Haem oxygenase limits Mycobacterium marinum infection‐induced detrimental ferrostatin‐sensitive cell death in zebrafish. (28th September 2021) - Luo, Kaiming; Stocker, Roland; Britton, Warwick J.; Kikuchi, Kazu; Oehlers, Stefan H.
Abstract : Iron homeostasis is essential for both sides of the host–pathogen interface. Restricting access of iron slows bacterial growth while iron is also a necessary cofactor for host immunity. Haem oxygenase 1 (HMOX1) is a critical regulator of iron homeostasis that catalyses the liberation of iron during degradation of haem. It is also a stress‐responsive protein that can be rapidly upregulated and confers protection to the host. Although a protective role of HMOX1 has been demonstrated in a variety of diseases, the role of HMOX1 in Mycobacterium tuberculosis infection is equivocal across experiments with different host–pathogen combinations. Here, we use the natural host–pathogen pairing of the zebrafish‐ Mycobacterium marinum infection platform to study the role of zebrafish haem oxygenase in mycobacterial infection. We identify zebrafish Hmox1a as the relevant functional paralog of mammalian HMOX1 and demonstrate a conserved role for Hmox1a in protecting the host from M. marinum infection. Using genetic and chemical tools, we show zebrafish Hmox1a protects the host against M. marinum infection by reducing infection‐induced iron accumulation and ferrostatin‐sensitive cell death. Abstract : Haem oxygenase 1 (HMOX1) is an essential regulator of iron homeostasis that mediates the first step of haem catabolism. HMOX1 is also a stress‐responsive protein that has been shown to have a protective role in several diseases. In this study, Stefan H. Oehlers and co‐authors identify hmox1a as the zebrafish ortholog of mammalian HMOX1. They show that zebrafish Hmox1a protects against Mycobacterium   marinum infection by clearing host haem and preventing host cell death at the infection site. The increased infection susceptibility of Hmox1a‐deficient zebrafish can be reversed with the small molecule ferrostatin, suggesting that Hmox1a prevents ferroptosis during M. marinum infection.